GLP-1-BASED THERAPIES BEYOND DIABETES: EMERGING CLINICAL APPLICATIONS AND FUTURE PERSPECTIVES - Anna Szeszko; Małgorzata Lubowiecka; Weronika Czernek; Magdalena Cichorzewska; Martyna Płachta; Rafał Wojtan (Archiv Euromedica, 2026)
Background Glucagon-like peptide-1 (GLP-1)-based therapies were initially developed for the treatment of type 2 diabetes mellitus, but their clinical use has expanded substantially because of their effects on body weight and obesity-related complications. GLP-1 receptor agonists, dual and triple receptor agonists, and GLP-1-containing combination therapies are now being evaluated across cardiovascular, hepatic, kidney, respiratory and musculoskeletal diseases, as well as other conditions with metabolic, neuroendocrine or behavioural components. Aim To critically summarise established and emerging clinical applications of GLP-1-based therapies beyond direct glucose lowering and to distinguish evidence-supported indications from preliminary or investigational uses. Materials and Methods A narrative review guided by the principles of the Scale for the Assessment of Narrative Review Articles was conducted. PubMed/MEDLINE, the Cochrane Library, major journal platforms, ClinicalTrials.gov and United States and European regulatory websites were searched for English-language evidence published between January 2015 and 10 July 2026. Seminal earlier studies were included when required. Randomised trials, observational studies, meta-analyses, guidance documents and regulatory materials were synthesised thematically. Results Fifty-three sources were included. Robust randomised evidence supports chronic weight management, reduction in the risk of progression to type 2 diabetes during active treatment in people with obesity and prediabetes, cardiovascular risk reduction in adults with overweight or obesity and established cardiovascular disease, and clinically relevant benefits in obesity-related heart failure with preserved ejection fraction and moderate-to-severe obstructive sleep apnoea. Histological improvements have been demonstrated in metabolic dysfunction-associated steatohepatitis with fibrosis, while semaglutide reduced major kidney outcomes in patients with type 2 diabetes and chronic kidney disease. In obesity-associated knee osteoarthritis, one phase 3 trial showed improvements in pain and physical function. Evidence for Parkinson disease and Alzheimer disease was inconsistent or negative, whereas evidence for alcohol use disorder and polycystic ovary syndrome remained preliminary. Many observed benefits may be mediated by weight loss, and direct organ-specific effects remain uncertain. Gastrointestinal adverse effects were most common, while long-term safety, durability after treatment discontinuation, preservation of muscle mass and physical function, and equitable access remain unresolved. Conclusions GLP-1-based therapies are increasingly used in the management of obesity and selected obesity-related chronic diseases. Their clinical value depends on the specific agent, dose, patient phenotype and outcome assessed. Weight-mediated improvements should be distinguished from direct pharmacological effects. Future organ-specific indications should be supported by reproducible clinical outcomes in clearly defined populations rather than by mechanistic plausibility, biomarker changes or the magnitude of weight loss alone.